Influence of metal uptake from fly ash on the growth of Jatropha Curcas plant: Bulk utilization approach - SEEMA RAJ; SUMEDHA MOHAN (International Journal of Pharma and Bio Sciences, 2018)
The presence of metals in fly ash is well researched. In the present work the metal uptake including heavy metals from fly ash by biodiesel plant Jatropha curcas was studied. For this study three samples of fly ash amended soil were prepared: Treatment 1- T1 (100% soil), Treatment 2- T2 (25% fly ash + 75% soil) and Treatment 3- T3 (50% fly ash + 50% soil), where sample size was 15 in all treatments. The biochemical and morphological parameters of J. curcas were studied for three consecutive years of plant growth in all treatments. Among all treatments, T3 treatment plants showed better growth due to the presence of nitrogen 11.73mg/g, protein 62.08%, sulphur 0.15%, reducing sugar 1230.59µg/g, chlorophyll-a 0.52mg/g, chlorophyll-b 0.41mg/g, carotenoids 0.27mg/g, total chlorophyll 0.93mg/g in leaves. The percent absorption of metals (Zn, Ca, Mg, Pb, Cu, Fe, Mn, Ni and Cd) by J. curcas plants were also taken in consideration by evaluating metal concentration in two stages. Correlation between plant growth and metal uptake was evaluated, which proved the significant effect of metal uptake on plant growth of J. curcas from T1 to T3. This research approaches the waste utilization and remediation of fly ash amended soil by accumulation of metals from base material.